Studying Entrepreneurship-as-Practice Visually: Data Strategies and Analytical Considerations - Zhao, W. G. Will; Ba, Lina (Frontiers in Psychology, 2022)
The objective of this essay is to forge a more explicit link between the vibrant "visual turn" and the burgeoning "practice turn" in entrepreneurship research. Specifically, we explore three key aspects of mobilizing visual methods for studying entrepreneurship as practice, i.e., data sources, collection strategies, and analytical considerations, highlighting the important theoretical and empirical promises that visual methods hold for said research. This essay bears implications for researchers and educators working at the intersection of entrepreneurship research, the practice theory, and visual methods.